O grupo escolar de Poconé-MT (1912-1922) : na contramão da escola modelar - Morais, Josiana Antônia Proença Amaral de (2022)
This master's research, entitled The Poconé-MT School Group (1912 -1922): on the opposite of the model school, is part of the Research Line Culture, Memory and Theories of Education of the Graduate Program in Education at the Federal University from Mato Grosso. Its aim is to understand the process of creation, implementation and the trajectory of School Group of Poconé, in the municipality of Poconé - MT, inquiring about the purposes that motivated and influenced the installation of this institution in the locality. The time frame refers to the year of implementation of the School Group in Poconé (1912) until the year in which it was again transformed into isolated schools (1922). To support the analysis, the concepts of Cultural History and the History of School Institutions were used in the works of Certeau (2002), Magalhães (2004), Sanfelice (2007) and Nosella and Buffa (2009), as well as the authors who discuss school groups in Brazil and Mato Grosso: Souza (1998), Silva (2006), Amâncio (2000), Sá (2006). To this end, messages from the presidents of the state of Mato Grosso, reports from the director of Public Instruction of the state and of the Poconé School Group, appointments and periodicals, among others, located in the Public Archive of the State of Mato Grosso, in the Hemeroteca of National Library and the Database of the Research Group History of Education and Memory were used. The analysis allowed us to understand that Poconé did not have the prerequisites established by the Public Instruction Regulations (1910), that is, it worked in a rented building without physical and hygienic conditions and with a lower number of students than stipulated, as well as it did not have the pedagogical material necessary for a School Group and, due to a specific culture of the Pantanal life, the school calendar was not followed. It is understood that the creation of Poconé School Group, a symbol of republican modernity, on the contrary to what was happening in other locations of the state, was favored by the fact that it was installed in the homeland and electoral stronghold of the President of the State, Joaquim Augusto da Costa Marques, who created it through Decree n. 580/1911. Being impracticable, due to the lack of physical structure, equipment and number of students, this school institution survived in the course of the first ten years without what was conceived for an institution of greatness, “the showcase of the Republic” (SILVA, 2006) and, therefore, it was extinguished in 1922, by Decree n. 585, April 29th, being replaced by five isolated schools.